2012
DOI: 10.1128/aem.07419-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Differentiation of Avian Mycoplasmas by Surface-Enhanced Raman Spectroscopy Based on a Silver Nanorod Array

Abstract: Mycoplasma gallisepticum is a bacterial pathogen of poultry that is estimated to cause annual losses exceeding $780 million. The National Poultry Improvement Plan guidelines recommend regular surveillance and intervention strategies to contain M. gallisepticum infections and ensure mycoplasma-free avian stocks, but several factors make detection of M. gallisepticum and diagnosis of M. gallisepticum infection a major challenge. Current techniques are laborious, require special expertise, and are typically plagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…49 Other studies showed that our SERS-based methods had equivalent-or-better detection limits than qPCR for analysis of pathogens in complex clinical samples. 50 Therefore, based on our previous experience, we feel confident that the methods described here can be extended to analyze biologically complex mixtures.…”
Section: Discussionmentioning
confidence: 80%
“…49 Other studies showed that our SERS-based methods had equivalent-or-better detection limits than qPCR for analysis of pathogens in complex clinical samples. 50 Therefore, based on our previous experience, we feel confident that the methods described here can be extended to analyze biologically complex mixtures.…”
Section: Discussionmentioning
confidence: 80%
“…9, 53 The current work is the first to use the LBL method to ensure preparation of whole, intact encapsulated mycoplasma cells for use in SERS classification studies. The high quality and reproducibility of the LBL SERS spectra, as seen in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…9, 30 The high discriminatory ability of LBL SERS seen in this study is similar to that seen when using Ag nanorod-based SERS methods to analyze the spectra of human and avian mycoplasmas, albeit with lower root mean square errors. 9, 53 …”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, Raman spectral signatures of multiple strains of avian mycoplasma species including Acholeplasma laidlawii , Mycoplasma gallinarum , Mycoplasma gallinaceum , Mycoplasma synoviae , and M. gallisepticum , and vaccine strains 6/85, F, and ts-11 were collected and processed by multivariate analysis to differentiate laboratory cultures of mycoplasma species [79]. A PLS-DA model classified the spectra for all species with 93 to 100% sensitivity and with similar specificity for all species except Mycoplasma synoviae , which was distinguishable with only 80% specificity.…”
Section: Detection Of Bacteriamentioning
confidence: 99%